The Effect of Various Enzymes on the Ultrastructure, Aggregation, and Clot Retraction Ability of Rabbit Blood Platelets - Hovig, Torstein (Thrombosis and Haemostasis, 1965)
The effect of various enzymes on rabbit blood platelets was studied with the following results :1. The proteolytic enzymes trypsin and papain destroyed the ability of the platelets to aggregate with (1) ADP and (2) suspensions of collagen particles. The aggregation ability was not restored by incubation of the platelets in plasma. The platelets treated with these enzymes did not adhere to tendon tissue in vitro.2. The clot retraction activity of the platelets treated with trypsin and papain was decreased. This effect was especially pronounced with the trypsinized platelets.3. In about 20% of the trypsinized platelets intracellular membrane systems appeared. Trypsin did not cause marked loss of platelet organelles and no obvious effect on the boundary membrane could be detected with the electron microscopical technique.4. No effect of hyaluronidase on the platelets could be found.5. Whereas no effect of lipase from wheat germ could be detected, phospho-lipase A caused pronounced ultrastructural changes within the platelets and the structure of the boundary membrane was altered. Corresponding to these findings release of substances from the platelets was observed by spectrophotometry (with absorption maximum at 260 ιημ) and release of ADP was demonstrated by a specific enzymatic test.6. Platelets treated with neuraminidase aggregated spontaneously when resuspended in citrated plasma or EDTA-plasma. This effect was probably not due to released ADP. It is concluded that besides protein, neuraminic acid (linked to protein) may be of fundamental importance for the aggregation properties of blood platelets.